The chemical content of Arabica coffee beans with the application of ethrell, NAA, and gibberellin to accelerate ripening in several varieties - Astuti, Yohana Theresia Maria; Dharmawati, Nuraeni Dwi; Santosa, Tri Nugraha Budi; Silalahi, Edo Hasiholan; Alfandi, Iqbal; Arifin, Zaenal (AGROMIX, 2024)
Introduction: Caffeine, antioxidants, and vitamin C are important compounds found in coffee beans. These chemical compounds affect the taste and aroma of coffee. The research aims to examine the effect of hormone application on the chemical content of coffee beans. Methods: The research was carried out at the people's coffee plantation in Kwadungan Gunung, Kledung, Temanggung, Central Java. The research uses an experimental method with two factors. Factor I variety consists of two varieties, namely Sigararutang and Yellow Catura. Factor II of the Plant Growth Regulators (PGR) application consists of four levels, namely: Control, ethrel, NAA, and gibberellin. Each treatment combination with 5 replications. The parameters observed were the number of fruit/ tree, the number of ripe fruit/ tree at the first harvest, caffeine content, vitamin C, antioxidant activity, sugar, and protein. Data were analyzed using ANOVA with the DMRT further test. Results: The number of coffee cherries of the Yellow Catura was better than the Sigarar Utang. The caffeine is better in Sigararutang in all PGR applications compared to other combinations. The antioxidant activity of Yellow Catura with the application of NAA and GA3 is better than other combinations. Vitamin C in Yellow Catura with GA3 application and control is better than other combinations. The protein in Yellow Catura with NAA application is better than other combinations. The sugar in Yellow Catura with all applications of PGR is better than the other combinations. Conclusion: PGR application and differences in varieties affect the chemical content namely caffeine, antioxidant activity, vitamin C, protein, and total sugar.